The Challenges and Problems of Law in the Welfare State in the Digital Age - Nanda Maharani Sukma; Eny Kusdarini; Marzuki Marzuki (Al-Makki Publisher, 2024)
The digital era presents significant challenges for the welfare state, particularly in relation to the legal framework. This research aims to identify and analyze the legal challenges and issues faced by the welfare state in the context of rapid technological advancement. Using a descriptive approach, this research employs a literature review of recent sources published in the last decade to ensure their relevance and accuracy. Key challenges identified include data protection and privacy issues, digitalization of social services, cybersecurity threats, and digital workforce regulation. In addition, the study also addresses emerging legal issues such as copyright infringement, money laundering through cryptocurrencies, and the inadequacy of existing cybercrime laws. The findings show that while technological developments offer opportunities to improve welfare services, they also create complexities that threaten equality and social justice. The need for a robust legal framework that can adapt to these changes is emphasized, highlighting the role of the state in protecting citizens' rights in both the physical and digital realms. In conclusion, this research underscores the urgent need for legal reforms that balance the rights of individuals with the well-being of society, ensuring that the benefits of digital technologies are shared equitably across society. This research ultimately contributes to the ongoing discourse on the intersection of law, technology and social welfare in the modern era.